Diets naturally rich in polyphenols improve fasting and postprandial dyslipidemia and reduce oxidative stress: a randomized controlled trial. Issue 3 (24th December 2013) - Annuzzi, Giovanni; Bozzetto, Lutgarda; Costabile, Giuseppina; Giacco, Rosalba; Mangione, Anna; Anniballi, Gaia; Vitale, Marilena; Vetrani, Claudia; Cipriano, Paola; Corte, Giuseppina Della; Pasanisi, Fabrizio; Riccardi, Gabriele; et al.
ABSTRACT: Background: The postprandial triglyceride-rich lipoprotein (TRL) concentration is a recognized independent cardiovascular disease risk factor. Diet is the natural approach for these postprandial alterations. Dietary polyphenols and long chain n−3 polyunsaturated fatty acids (LCn3s) are associated with a lower cardiovascular disease risk. Objective: This randomized controlled study evaluated, in persons with a high risk of cardiovascular disease, the effects of diets naturally rich in polyphenols and/or marine LCn3s on plasma TRLs and urinary 8-isoprostane concentrations, a biomarker of oxidative stress. Design: According to a 2 × 2 factorial design, 86 overweight/obese individuals with a large waist circumference and any other component of the metabolic syndrome were randomly assigned to an isoenergetic diet 1 ) poor in LCn3s and polyphenols, 2 ) rich in LCn3s, 3 ) rich in polyphenols, or 4 ) rich in LCn3s and polyphenols. The diets were similar in all other components. Before and after the 8-wk intervention, fasting and postmeal TRLs and 8-isoprostane concentrations in 24-h urine samples were measured. Results: Dietary adherence was good in all participants. Polyphenols significantly reduced fasting triglyceride concentrations (2-factor ANOVA) in plasma ( P = 0.023) and large very-low-density lipoproteins (VLDLs) ( P = 0.016) and postprandial triglyceride total area under the curve in plasma ( P = 0.041) and large VLDLs ( P = 0.004). LCn3s reduced postprandial chylomicron cholesterol and VLDL apolipoprotein B-48. The concentrations of urinary 8-isoprostane decreased significantly with the polyphenol-rich diets. Lipoprotein changes induced by the intervention significantly correlated with changes in 8-isoprostane. Conclusions: Diets naturally rich in polyphenols positively influence fasting and postprandial TRLs and reduce oxidative stress. Marine LCn3s reduce TRLs of exogenous origin. Through their effects on postprandial lipemia and oxidative stress, polyphenols may favorably affect cardiovascular disease risk. This trial was registered at http://www.clinicaltrials.gov as NCT00781365.